Pretherapeutic laboratory findings, extent of metastasis and choice of treatment as prognostic markers in ocular melanoma– a single centre experience. (12th October 2012) - Schicher, N.; Edelhauser, G.; Harmankaya, K.; Schindler, K.; Gleiss, A.; Pehamberger, H.; Hoeller, C.
Abstract Background Uveal melanoma is the most common intraocular neoplasm with a high tendency to metastasize predominantly to the liver. Prognostic parameters for progression and overall survival are not well defined. The aim of this study was to assess the value of pretherapeutic serum levels of C‐reactive protein (CRP), lactate dehydrogenase, albumin and fibrinogen in patients with uveal melanoma and to evaluate their significance as prognostic parameters for survival. Methods Forty‐nine patients with metastatic uveal melanoma treated between 2000 and 2010 were retrospectively analysed. The potential influence of levels of CRP, lactate dehydrogenase, fibrinogen and albumin as well as other commonly known prognostic variables on progression‐free and overall survival were investigated. Results Patients' age and treatment with systemic chemotherapy were the only variables to show significant influences on progression‐free and overall survival in a univariate analysis. Multivariate analysis confirmed the influence of these variables on progression‐free survival, presence of metastasis, pretherapeutic CRP levels and treatment with systemic chemotherapy were associated with overall survival. Conclusion In this patient cohort elevated pretherapeutic CRP and extent of metastasis are independent prognostic factors for decreased overall survival, whereas treatment with systemic chemotherapy showed a significant association with improved overall survival.